Medical students’ attitudes toward providing patients with audio recordings of their medical encounters: a cross-sectional online survey - Cheyenne Topf; Marina Buzo; Pola Hahlweg; Isabelle Scholl (BMC Medical Education)
Abstract Background Medical encounters often involve complex information that can be challenging to process, especially in emotionally charged situations. Providing patients with audio recordings of their medical encounters, termed consultation recordings, has shown promising benefits such as improved information recall and understanding. In prior research, patients largely reported favorable attitudes toward consultation recordings; physicians were more skeptical, particularly regarding legal risks. To date, consultation recordings are rare in Germany. This study aimed at understanding medical students’ attitudes toward consultation recordings, as they are the healthcare professionals of the future and could therewith play a crucial role in further implementation efforts. Methods We conducted a nationwide cross-sectional quantitative online survey with medical students in Germany, assessing attitudes toward and desire for future consultation recordings. Data was analyzed using descriptive statistics. Results Two hundred twenty-two participants were included. 56% of participants expressed positive attitudes toward consultation recordings, acknowledging benefits such as information recall and preparation for follow-up consultations. However, they also expressed significant concerns about potential misuse, legal implications, and physicians feeling pressured. About 16% of participants expressed a clear willingness to offer consultation recordings in the future, while 44% were hesitant. Conclusions Our findings that medical students recognize potential benefits of consultation recordings, while simultaneously expressing concerns about this intervention, are comparable to results from studies conducted in physician samples. Medical students’ limited clinical experience and the low prevalence of consultation recordings in Germany likely contribute to these apprehensions. These mixed attitudes could be addressed by providing opportunities for positive experiences with consultation recordings during medical and postgraduate education as well as in clinical practice. Providing role models who support patient-centered care could also foster greater acceptance. Future research should focus on the integration of patient-centered interventions such as consultation recordings in the medical curricula. Overall, consultation recordings have the potential to become a valuable tool in routine healthcare if current barriers are effectively addressed.